APPLICATIONS OF DIFFERENTIAL SUBORDINATION AND SUPERORDINATION - Ganesamoorthy, C.; Marikkannan, N.; Jeyaraman, M. P. (IndoMS, 2008)
In the present investigation we obtain asndwich theorems for certain subclass of analytic functions defined by convolution. Our results generalizes several well known results.DOI :Â http://dx.doi.org/10.22342/jims.14.1.62.47-56